(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
As a result of the work carried out, it was found out that the hydrothermal metasomatites of the secondary quartzite formations of Amulsar arose from the andesites propylitized in the hypabysical facies. What is spatially associated with the mineralization of gold and silver. The rutile facies of Amulsar are predominant, and the sericite and alunite facies have extremely limited development. A schematic map of the distribution of them is given. Geological and petrographic studies show that the secondary quartzites of Amulsar arose under conditions of acid leaching with the post-volcanic hydrotherms of the andesites of the Upper Eocene-Lower Oligocene.